Enhancement of railway automatic equipment by means of computer networks implementation - Amochaeva, G.P.; Omarbekova, G.I.; Seisenbayeva, G.S. (Publishing House of the KarSU named after E.A.Buketov, 2015)
The computer systems operational management of train traffic, intended for backbone and industrial vehicles are examining in this article. This is system based on the distributed controlled points and centralized traffic control system which based on microcomputers and programmable controllers. Its composition, functionality for practical use at the stations of the Karaganda branch of JSC "Temir Zholy" were analyzed in this work. The future of electric centralization determined by the transition from a microprocessor-based relay systems. The introduction of microprocessor systems automates operations supervisory personnel, contributes to the creation of automated systems for traffic control, have higher rates of efficiency through integration.
Keywords: auto locking; block telesignalization; distributed controlled points; communication links; semi-automatic; lock